CRITICAL THINKING SKILLS AND CREATIVITY ENHANCEMENT IN 7th GRADE STUDENTS THROUGH PBL MODEL AND JAS APPROACH - Fatimah, S. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2015)
This research aim is to improveÂ critical thinking skill dan creativity of student at VIIC classÂ in SMP 2 Kudus academic year 2013/2014 by implementingÂ problem-based learning (PBL) with Jelajah Alam Sekitar (JAS) approach. The study design used is classroom action research is conducted inÂ 2 cycles. The first cycle apply PBL with JAS approach in which students conduct direct exploration to environment and in the second cycle students conduct direct and indirect exploration. The results showed that PBL model with JAS approach able to improve studentsâ critical thinking skills amounted to 74. 35% and enhance studentsâ creativity amounted to 66.96%. It can be concluded that the PBL model with JAS approach able to improve critical thinking skills and creativity of students effectively.